2023
DOI: 10.21608/sinjas.2023.192393.1187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Jerusalem artichoke as a functional ingredient in cookies production

Abstract: Jerusalem artichoke (JA) tubers are rich in minerals, fibers and inulin, a unique polysaccharide stored in them instead of starch. In this study, JA tubers were dried and ground into flour, which was then used to substitute 2.5, 5, 7.5 and 10% of wheat flour to prepare functional cookies using the previously mentioned functionality (minerals and fibers). The chemical composition of cookies was investigated, as well as the effects of substituting wheat flour for JA tubers flour (JAF) on it. JAF increased the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These results are consistent with (Mohamad Nor et al, 2021), who observed increasing diameter values with a higher substitution level of wheat flour with sweet potato (a gluten-free ingredient). Physical properties of cookies including spread ratio, specific volume, and color showed marginal changes due to higher fiber and moisture contents in the prepared cookies (Solayman et al, 2023). A gradual increase in thickness was also noted with the increase in substitution level of QF and JAF, as the maximal thickness value was that of T8 samples (0.547cm) and the minimal thickness value was that of the control sample (0.527cm).…”
Section: Physical Properties Of Biscuitsmentioning
confidence: 86%
See 2 more Smart Citations
“…These results are consistent with (Mohamad Nor et al, 2021), who observed increasing diameter values with a higher substitution level of wheat flour with sweet potato (a gluten-free ingredient). Physical properties of cookies including spread ratio, specific volume, and color showed marginal changes due to higher fiber and moisture contents in the prepared cookies (Solayman et al, 2023). A gradual increase in thickness was also noted with the increase in substitution level of QF and JAF, as the maximal thickness value was that of T8 samples (0.547cm) and the minimal thickness value was that of the control sample (0.527cm).…”
Section: Physical Properties Of Biscuitsmentioning
confidence: 86%
“…The textural characteristics of biscuits prepared from yellow corn flour, QF at different concentrations (20 and 40%) with 20% chickpea flour and JAF at (20 and 40%) with 20% chickpea flour with reducing 15% and 30% of sugar as shown in Table 8. JAF increased the moisture content of cookies, resulting increased hardness and fracturability (Solayman, et al, 2023). Biscuits containing QF (T1 and T2) displayed increased hardness (17.70 N and 19.34 N, respectively) compared to the control (15.13 N).…”
Section: Water Activity Of Biscuits Formulated With Partially Quinoa ...mentioning
confidence: 99%
See 1 more Smart Citation